Assembled Worlds: New Campo Marzio – Piranesi in the Age of AI. (7th April 2022) - Rehm, M Casey; Jovanovic, Damjan
Abstract: New Campo Marzio is a collaboration between Damjan Jovanovic and Lidija Kljakovic of lifeforms.io and M Casey Rehm of Studio Kinch. Jovanovic and Rehm are also faculty at the Southern California Institute of Architecture (SCI‐Arc). They have used AI and game engines to create a new vision for the iconic public space in Rome, inspired by and inputting data from Giovanni Battista Piranesi's seminal architectural plan of it from 1762.